UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN JELATANG (Urtica dioica L.) TERHADAP BAKTERI Escherichia coli - Dia Moudy Villiya P.; Siti Maimunah (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Jelatang (Urtica dioica L.) is one of medicinal plants. Jelatang leave contain some compound as alkaloids, flavonoids and saponins. Those compounds are known to have antibacterial activity. This work was to study the antibacterial activity of extract ethanol jelatang leave (Urtica dioica L.) against Escherichia coli. The sample used jelatang leave (Urtica dioica L.) take from the environment Afd VI Kebun Tandun, Kampar, Kecamatan Tapung Hulu, Riau. The research used experimental method with stages as jelatang leave collection, identification of plant, manufacture of simplicia, extract making, skrining of phytochemicals, characterization of simplicia and antibacterial activity test.Powder of jelatang dried were extracted leaves by maceration method using ethanol 96%. Testing antibacterial activity by diffusion method using paper disc. The result of characterization of leaves jelatang powder of jelatang dried was found 9,19% water content, water soluble sari 24,94%, ethanol soluble sari 7,48%, total ash content of 18,46% and acid unsaturated ash content 6,49%. Antibacterial activity test showed that jelatang leave (Urtica dioica L.) ethanol extract could inhibited the growth of Eschericia coli has inhibitory power that is diameter as: extract 20% (5,4 mm) , 22% (6 mm), 24% (7,4 mm) 26% (7,8 mm). Ethanol extract jelatang leave have antibacterial activity the highest concentration 26% as 7,8 mm include medium category